CONCEPTUALIZATION OF MONEY IN ENGLISH AND RUSSIAN PROVERBS: A COGNITIVE PERSPECTIVE - Oleneva, Polina (Proverbium - Yearbook, 2023)
The present article is an attempt to investigate the metaphorical dimension in English and Russian money proverbs. A sample of English and Russian proverbs have been selected from various sources such as dictionaries, previous research, and the internet. The analysis was within the framework of the Conceptual Metaphor Theory as suggested by Lakoff and Johnson (1980), and the force money system by Kövecses (2018). The analysis showed that the money concept in English and Russian proverbs can constitute both the source domain and target domain. Also, it was found that both languages mostly exhibit similarities in the conceptual metaphors that trigger off money proverbs. Nevertheless, In English proverbs, money as a source domain was slightly higher than it is in the Russian proverbs of money. On the contrary, Russian money proverbs showed that money constituted a target domain roughly more than it did in the English proverbs of money. This was an endeavour to explore conceptual metaphors in money proverbs in proverbs in two distinct languages. It is recommended to investigate the metaphors in further areas of proverbs such as health and human relationships between English and Russian.